Multiscale simulation of atomization with small droplets represented by a Lagrangian point-particle model. (November 2015) - Ling, Y.; Zaleski, S.; Scardovelli, R.
Highlights: A multiscale multiphase flow model for atomization simulations is proposed. The large-scale interfaces are resolved by the Volume-of-Fluid (VOF) method. The small droplets are represented by the Lagrangian point-particle (LPP) model. A series of multiphase flow problems are considered to validate the model. The model is applied to simulate the gas-assisted atomization experiment. Abstract: Modeling and simulation of atomization is challenging due to the existence of a wide range of length scales. This multiscale nature of atomization introduces a fundamental challenge to numerical simulation. A pathway to comprehensive modeling is still to be found. The present study proposes a multiscale multiphase flow model for atomization simulations, where the large-scale interfaces are resolved by the Volume-of-Fluid (VOF) method and the small droplets by the Lagrangian point-particle (LPP) model. Particular attention is focused on the momentum coupling between LPP and resolved flow and the conversion between droplets represented by VOF and LPP. A series of multiphase flow problems are considered to validate the model. The results obtained by a number of simulations are compared against direct numerical simulation (DNS) results and experimental data. In particular, the model is applied to simulate the gas-assisted atomization experiment, and the numerical results are compared to the experimental measurements for a quantitative validation.